Dry sliding wear behavior of 316 L stainless steel produced by laser powder bed fusion: A comparative study on test temperature. (March 2023) - Khan, Hamaid Mahmood; Yilmaz, Mustafa Safa; Karabeyoğlu, Süreyya Sencer; Kisasoz, Alptekin; Özer, Gökhan
Abstract: Laser powder bed fusion (LPBF) is becoming more popular and widely acceptable class of the additive manufacturing processes for metallic objects. The impact of test temperatures, sliding speed, and loading conditions on the wear behavior of LPBF generated 316 L stainless steel is investigated in this work. The findings revealed that the effect of all the three wear test conditions was significant on the coefficient of friction (COF) and wear rate of additive samples. The COF and wear rate were found to be reduced at 400 °C in all samples when compared to room temperature, which was attributed to oxidation of the exposed surface, which serves as a lubricant and shields the surface from additional material loss. Moreover, the wear rate and CoF were found to increase with the increasing normal load and reducing sliding speed. Graphical Abstract: ga1 Highlights: The as-built micro- and macro-based surface features strongly influence the wear performance of LPBF 316 L SS samples. Higher working temperatures of about 400 oC is conducive for wear performance due to passive oxide layer formation Increasing sliding speed results in higher wear rate due to the introduction of high thermal energy into system. Increasing normal loads causes material to erode more due to higher contact pressure